Leishmania Immunity: Advancing Immunotherapy and Vaccine Development - Nnamdi M. Ikeogu; Gloria N. Akaluka; Chidalu A. Edechi; Enitan S. Salako; Chukwunonso Onyilagha; Aida F. Barazandeh; Jude E. Uzonna (Microorganisms, 2020)
Parasitic diseases still constitute a major global health problem affecting billions of people around the world. These diseases are capable of becoming chronic and result in high morbidity and mortality. Worldwide, millions of people die each year from parasitic diseases, with the bulk of those deaths resulting from parasitic protozoan infections. Leishmaniasis, which is a disease caused by over 20 species of the protozoan parasite belonging to the genus Leishmania, is an important neglected disease. According to the World Health Organization (WHO), an estimated 12 million people are currently infected in about 98 countries and about 2 million new cases occur yearly, resulting in about 50,000 deaths each year. Current treatment methods for leishmaniasis are not very effective and often have significant side effects. In this review, we discussed host immunity to leishmaniasis, various treatment options currently being utilized, and the progress of both immunotherapy and vaccine development strategies used so far in leishmaniasis. We concluded with insights into what the future holds toward the fight against this debilitating parasitic disease.